Practice visits as a tool in quality improvement: acceptance and feasibility. Issue 3 (1st September 1999) - van den Hombergh, P; Grol, R; van den Hoogen, H J; van den Bosch, W J
Abstract : OBJECTIVE: To evaluate the feasibility and acceptance of (a) two programmes of assessment of practice management in a practice visit: mutual practice visits and feedback by peers versus visits and feedback by non-physician observers and (2) the practice visit method used in these programmes (the visit instrument to assess practice management and organisation (VIP)--a validated Dutch tool). DESIGN: Prospective, randomised intervention study with the two programmes, follow up after one year. General practitioners (GPs) were visited after each programme and after the revisits by non-physician observers a year later. SETTING: General practices in the Netherlands in 1993 and 1994. SUBJECTS: A total of 90 GPs in 68 practices. At follow up after 1 year there were 81 GPs in 62 practices. MAIN MEASURES: Scores (mainly five point scales) for questions on appreciation and acceptance; after the follow up visit a year later, scores for questions on feasibility and practicality of the improved procedure and feedback report. RESULTS: Data of 44 mutual visits by peers were compared with data of 46 visits by non-physician observers. A visit by a non-physician observer was appreciated significantly more. After the practice visit at one year follow up, the participants reported to have appreciated the visit and the feedback report and to prefer feedback of a non-physician observer to that of a peer. Participants' reports on the procedure and the presentation of the feedback provided clues for the improvement of visit procedures. CONCLUSIONS: A practice visit and feedback by a non-physician observer is more appreciated than a visit and feedback by a colleague. A practice visit with the VIP by a non-physician observer is a simple, easy, and well accepted method for assessing practice management.